Vaccination generates broadly cross-neutralizing antibodies to the HIV Env apex - Javier Guenaga; Monika Ádori; Shridhar Bale; Swastik Phulera; Ioannis Zygouras; Fabian-Alexander Schleich; Xaquin Castro Dopico; Sashank Agrawal; Miyo Ota; Richard Wilson; Jocelyn Cluff; Tamar Dzvelaia; et al. (Nature, 2026)
Abstract As a chronically replicating virus, HIV has evolved extreme sequence variability and effective shielding of functionally constrained spike protein determinants by host-derived glycans 1 . Broadly neutralizing antibodies, although rare, can be isolated from people living with HIV, revealing conserved envelope glycoprotein (Env) sites as key targets for vaccine development 2–4 . One such target is the apex of the Env spike. Here we identify a vaccination strategy using heterologous HIV Env trimers covalently coupled to liposomes for multivalent display that resulted in the elicitation of cross-neutralizing HIV serum antibody responses in all trimer-liposome-immunized non-human primates. Critically, we isolated monoclonal antibodies from multiple macaques that cross-neutralize divergent HIV clinical isolates. High-resolution cryogenic electron microscopy structural analyses of monoclonal antibodies from four different macaques demonstrate that they target the Env trimer apex in a manner highly similar to that of the human-infection-elicited, apex-directed broadly neutralizing antibody PG9, representing a substantial advance in HIV vaccine development.